Everyday teacher leadership : taking action where you are - Collay, Michelle (Jossey-Bass leadership library in education., 2011)
The essential guidelines for leading effective change in your school. From an education expert comes a much-needed resource that gives teacher leaders the strategies and tools they need to improve their practice and assume new leadership roles in their schools. The author outlines the everyday acts of teacher leadership and shows how to lead effectively through collaboration. The book also contains suggestions for leading change beyond the classroom. Discusses what works when taking on the role of teacher leader in a school. Contains proven strategies and tools for implementing school change.